2012
DOI: 10.1162/jocn_a_00230
|View full text |Cite
|
Sign up to set email alerts
|

A Sensorimotor Network for the Bodily Self

Abstract: Neuroscientists and philosophers, among others, have long questioned the contribution of bodily experience to the constitution of self-consciousness. Contemporary research answers this question by focusing on the notions of sense of agency and/or sense of ownership. Recently, however, it has been proposed that the bodily self might also be rooted in bodily motor experience, that is, in the experience of oneself as instantiating a bodily structure that enables a specific range of actions. In the current fMRI st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 78 publications
7
69
0
2
Order By: Relevance
“…Implicit and explicit recognition of the bodily self dissociate: only implicit recognition of the bodily self, mapped in motor terms, facilitates implicit bodily self processing. A subsequent fMRI study [55] based on a similar hand mental rotation task showed that a bilateral cortical network formed by the supplementary and pre-supplementary motor areas, the anterior insula and the occipital cortex activated during processing of participants' own hands. Furthermore, the contralateral ventral premotor cortex was uniquely and specifically activated during the mental rotation of participants' own dominant hand.…”
Section: From the Bodily Self To Intersubjectivitymentioning
confidence: 99%
“…Implicit and explicit recognition of the bodily self dissociate: only implicit recognition of the bodily self, mapped in motor terms, facilitates implicit bodily self processing. A subsequent fMRI study [55] based on a similar hand mental rotation task showed that a bilateral cortical network formed by the supplementary and pre-supplementary motor areas, the anterior insula and the occipital cortex activated during processing of participants' own hands. Furthermore, the contralateral ventral premotor cortex was uniquely and specifically activated during the mental rotation of participants' own dominant hand.…”
Section: From the Bodily Self To Intersubjectivitymentioning
confidence: 99%
“…A subsequent fMRI study by Ferri et al [31] using a similar hand mental rotation task demonstrated that a bilateral cortical network formed by the supplementary and presupplementary motor areas, the anterior insula and the occipital cortex was activated during processing of participants' own hands. Furthermore, the contralateral ventral premotor cortex (vPMC) was uniquely and specifically activated during mental rotation of participants' own dominant hands.…”
Section: The Motor Roots Of the Minimal Bodily Selfmentioning
confidence: 99%
“…As shown in the previous section, the human vPMC is activated during the implicit processing of one's own hand [31]. Given that the vPMC appears to be hypofunctional as well as negatively correlated with self-experience disturbances in schizophrenia [55], and since it has been demonstrated that patients show a defective implicit sense of their bodily self [53], we hypothesize that the defective anticipatory touch displayed by schizophrenic patients as demonstrated by the study of Ferri et al [56] might share the same premotor origin [64].…”
Section: Bodily Self and Schizophrenia: Loss Of Implicit Self-knowledmentioning
confidence: 99%
“…In a subsequent fMRI study [27], we tested the hypothesis that the sensorimotor system plays a pivotal role in the implicit self/other distinction during the laterality judgment task. We highlighted a neural network for the general representation of the bodily self encompassing the supplementary and presupplementary motor areas, the anterior insula, and the occipital cortex, bilaterally.…”
Section: Minimal Self and Bodily Self: Looking For The Basic Experienmentioning
confidence: 99%